SALVATION WITHOUT CULTIC MERIT: THE CHILD FIGURE IN MATTHEW 18-19 AS DECONSTRUCTION OF TEMPLE MERITOCRACY - Felicia Oetomo; Jonathan Octavianus (CV Naskah Aceh, 2026)
This study explores the significance of the